2008
DOI: 10.1007/s00520-007-0375-z
|View full text |Cite
|
Sign up to set email alerts
|

Information to cancer patients: a questionnaire survey in three different geographical areas in Italy

Abstract: In Italy, the cultural attitude towards communication in oncology is changing on both the physician and the patient side. There are still significant geographical differences, but there is a general trend suggesting improved awareness about diagnosis and treatment, with the notable exception of prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
45
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(53 citation statements)
references
References 25 publications
5
45
3
Order By: Relevance
“…In a different study that was conducted with 147 patients with metastatic cancer in Italy, 72.4 % of the patients did not have appropriate awareness of prognosis [39]. This latter finding is relatively more consistent with our study.…”
Section: Discussionsupporting
confidence: 82%
“…In a different study that was conducted with 147 patients with metastatic cancer in Italy, 72.4 % of the patients did not have appropriate awareness of prognosis [39]. This latter finding is relatively more consistent with our study.…”
Section: Discussionsupporting
confidence: 82%
“…
The article by Bracci et al on information to cancer patients in three different geographic areas in Italy, published in this issue of our journal, provides empirical evidence that attitudes and practices of disclosure to cancer patients have evolved in Italy [3]. A shift toward truth telling began in Italy and in many other countries in the late 1980s-early 1990s [26,32].
…”
mentioning
confidence: 96%
“…The study also examined different patient-doctor relationship styles, which are also evolving in countries where paternalism had traditionally been dominant in clinical medicine, and explored their link with their patients' information preferences and satisfaction [3,29]. Additional studies recently performed in Italy outside the field of oncology also indicate that open communication of diagnosis and treatment options is now common in other chronic, severe, often life-threatening illnesses [10].Patients in Bracci's study were treated in different geographic areas of Italy at three large teaching hospitals [3]. Within the context of teaching hospitals or specialized oncologic units, cancer patients are naturally exposed to more information than those who are treated at small local hospitals or in general wards or outpatient clinics.…”
mentioning
confidence: 99%
“…Although patients vary in the degree to which they want to be medically informed and to thereby participate in the decision-making process, surveys of patient preferences indicate that the overwhelming majority of patients in Western countries [11][12][13][14][15][16][17][18][19], and substantial proportion of patients in nonWestern countries [13,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], want disclosure of information to participate in the decision-making process. Universally, recent survey data of patient preferences demonstrate substantial heterogeneity of preferences that are not individually predictable by geography, culture, age, race, sex or educational level [11][12][13][14][15][19][20][21][22][23][24][25][26][27][28][29][30]…”
mentioning
confidence: 99%
“…Universally, recent survey data of patient preferences demonstrate substantial heterogeneity of preferences that are not individually predictable by geography, culture, age, race, sex or educational level [11][12][13][14][15][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]39]. Furthermore, studies that have evaluated the concordance between patient preferences on one hand and family member perception of patient preferences on the other hand have demonstrated that family members commonly underestimate the amount of information that patients desire about their condition and the degree to which they want to be involved in decisionmaking [32,37,[40][41][42][43][44].…”
mentioning
confidence: 99%